Establishment of an immortalized yak granulosa cell line: in vitro tool for understanding the molecular processes of ovarian follicle development - Wen, Xiao; Zhou, Jia; Yue, Shuangming; Zhang, Jun; Chen, Yuanyuan; Wang, Zhisheng; Wang, Lizhi; Peng, Quanhui; Xue, Bai (Frontiers in Veterinary Science, 2024)
The yak, a unique species of cattle found exclusively on the western plateau of China, is a valuable source of livelihood for local residents. However, their low fecundity restricts the expansion of yak farming, whereas regional factors limit studies on yak breeding. Granulosa cells (GCs), which provide essential steroid hormones and growth factors for oocytes, have been the focus of many studies on the mechanisms of follicular growth and atresia. This study, aimed to establish an immortalized cell line model that could serve as a tool for future studies on the mechanisms of ovarian follicle development in yaks. First, we isolated primary yak granulosa cells (yGC) and evaluated their replicative senescence after continuous in vitro subculturing. Subsequently, an immortalized culture method for primary yGC was explored and a new cell line model was established to study the mechanism of follicular development in vitro. We used a mammalian gene expression lentivirus vector to transfer the simian virus 40 large T antigen (SV40T) into primary yGC to obtain an immortalized cell line. The immortalized yGC were morphologically identical to the primary yGC, and cell proliferation and growth were normal within a limited number of generations. Follicle stimulating hormone (FSH) receptor, a specific marker for GCs, was positively expressed in immortalized yGC. Furthermore, the immortalized yGC retained the ability of GCs to synthesize estradiol and progesterone and expressed genes related to steroid synthesis. The establishment of immortalized yGC opens up a myriad of possibilities for advancing our understanding of yak reproductive biology and improving yak breeding strategies.